Otocephaly revealed: A case study of a rare facial anomaly - Kumble, Ali; Phadke, Abhishek K; Raikar, Poonam; Siriac , Anciline (Indian Journal of Case Reports, 2025)
Otocephaly (OC) is a rare malformation characterized by the association of agnathia (agenesis of mandible) or mandibular hypoplasia, melotia (anteromedial malposition of ears), microstomia (small mouth), aglossia or microglossia (absent or rudimentary tongue). We present an extremely preterm/very low birth weight/female baby born to a G2P1IUD1 mother. The baby did not cry at birth. APGAR was 3 at 1 min and 1 at 5 min. On examination, the baby had multiple craniofacial abnormalities including an absent mandible, small mouth, rudimentary tongue, ventromedian malposition of ears, and bilateral choanal atresia. Mother had gestational diabetes mellitus and severe polyhydramnios. No similar history in the family. Within 30 s of life, the baby became cyanotic. Bagging with mask and intubation was tried but resuscitation was not successful due to upper airway malformation. The baby had bradycardia and expired at 20 min of life.